The third Maccabiah, Israel, 27-9-1950 - 8-10-1950 : souvenir book, volume 1 - Maccabi World Union (Tel-Aviv, 1950)
Bibliotheek Camille Huysmans
Engels
Hebreeuws
Brochure
Keywords: sportmanifestaties; joden; Israël